Comparative Analysis Of The Bioethanol Yield And Components Of Sugar Extracted From Oil Palm Frond Under Different Prehydrolysis Treatments - Diyanilla, Dissanayake Mudiyanselage Rushan Lakshitha Bonuwan (2021)
This study was designed to produce a high bioethanol yield from OPF adopting eco-friendly and viable pretreatment methods, which are acid, autohydrolysis, alkaline, alkaline peroxide, and alkaline peroxide pretreatment coupled with acidified sodium chlorite (ASC) pretreatment